Analisis Wacana Iklan Minuman pada Media Internet - Putu Tia Aprilia Christandian; I Wayan Simpen; Anak Agung Putu Putra (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
Drink advertising is one of media that utilizes the biggest grammatical in promotional activities. The varian of discourse uses a choice of certain lingual units are composed of structure to achieve advertising purpose. This study aims to determine the cohesion parts, structure, and the aims of the beverage advertising through the discourse analysis approach. Data ware taken by observing the units beverage advertisement on internet. The qualitative approach is used to tell data descriptively and analyzed by agitation and matching methods. The results show (1) grammatical cohesion, namely: ellipsis, conjunctions, and noun repetition in lexical cohesion, (2) discourse structure is not equipped with a cover Minute Maid, Lemon Lime Sprite, and Coca-Cola. The dominant opening section aims to attract consumers' interest through the questions are given, and use propositions to attract special attention by writting customers’ name on Coca-Cola taq. The objective approach widely used in body of Lemon Lime Sprites, Yoo-Hoo Chocolate Drink, and Muscle Milk. Then, the advertising discourse has a closing part namely Yoo-Hoo Chocolate Drink uses hard technique, and Muscle Milk has subtle technique.